2023
DOI: 10.3389/fgwh.2022.958617
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and associated factors of adverse perinatal outcomes among women with oligohydramnios at 3rd trimester at University of Gondar comprehensive specialized hospital, North West Ethiopia

Abstract: BackgroundOligohydramnios is a pregnancy condition characterized by low volume of amniotic fluid. Based on ultrasound measurement, it is defined as a single maximum vertical pocket of liquor less than 2 cm or summation of four quadrants vertical pockets of liquor measurement less than 5 cm. It is associated with multiple adverse perinatal outcomes (APO) and complicates 0.5%–5% of pregnancies.ObjectiveTo assess magnitude and associated factors of adverse perinatal outcome among women with oligohydramnios at 3rd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
2
0
0
Order By: Relevance
“…The present study showed the most common indication for C/S was fetal distress (42.9%) which is similar to the studies conducted by Molla M et al [33] showed that the most common indication for C/S was fetal distress in pregnant women with oligohydramnios ( 40.3%) and Amin A et al [34] observed that the most common indication for C/S was fetal distress (47.5%). On the other hand, Niamrat T et al [32] reported a low rate of fetal distress for C/S ( 14.7%) which might be due to closed monitoring in antepartum and intrapartum pregnant women who had oligohydramnios.…”
Section: Discussionsupporting
confidence: 90%
“…The present study showed the most common indication for C/S was fetal distress (42.9%) which is similar to the studies conducted by Molla M et al [33] showed that the most common indication for C/S was fetal distress in pregnant women with oligohydramnios ( 40.3%) and Amin A et al [34] observed that the most common indication for C/S was fetal distress (47.5%). On the other hand, Niamrat T et al [32] reported a low rate of fetal distress for C/S ( 14.7%) which might be due to closed monitoring in antepartum and intrapartum pregnant women who had oligohydramnios.…”
Section: Discussionsupporting
confidence: 90%
“…Similar observations were found by Saxena et al where low birth weight babies were found in (51.43%) of patients and Panda et al showing LBW in 32% of patients. 21,22 NICU admission was required in almost 26.6% of the newborns correlating with 26.1% in the study by Molla et al and 28% in the study by Rita et al 14,23 No neonate required NICU admission in the study by Nankali Anisodowlel et al but they found meconium-stained liquor in around 20% of the cases which was comparable to our findings. 24 We found foetal distress in 17% of the cases, slightly higher than the study by Jagatia et al and lower than the study by Ray et al who found it to be 41%.…”
Section: Discussionsupporting
confidence: 89%
“…In the study by Rachakonda et al 76% patients were in the age group of 20-29 years. 11 More than half of our patients (55%) were primigravida which was almost similar to the incidence of 56% reported by Bhat et al 12 This higher incidence in primigravida as compared to multigravida was similar to the study by Twesigomwe et al 8 A higher incidence of 52% was also reported by Jagatia et al and 51% by Molla et al 13,14 Reasons postulated for higher occurrence of oligohydramnios in primigravidae are that disorders of pregnancy are exaggerated in primigravidas compared to multigravidas. Moreover, some complications, such as hyperemesis gravidarum, and infections (e.g., malaria), have been reported to be associated with oligohydramnios.…”
Section: Discussionsupporting
confidence: 85%
“…3 Studies have linked oligohydramnios with complications such as meconium aspiration, intrauterine growth restriction, stillbirth, and neonatal mortality. [4][5][6] Moreover, it heightens the likelihood of maternal complications, necessitating interventions like induced labor and cesarean deliveries. 2 Despite the established association between oligohydramnios and adverse outcomes, the impact of isolated borderline oligohydramnios remains a subject of debate.…”
Section: Introductionmentioning
confidence: 99%